Iloilo General Hospital a project feasibility study - Bayona, Suzy Lyn; Canete, Ray Omega; Chiu, Rica Pear; Jampazar, Shermila; Natividad, Amelin; Sison, Isis; Tan, Lelanie; Villanueva, Levites
A project feasibility study refers to the systematic and thorough analysis of all factors to determine the viability of aa proposed business undertaking. This paper endeavors to study the practicability and profitability of creating another hospital in Iloilo City. The proposed project shall be situated at corner Diversion Road and Jalandoni Extension. An introduction will furnish the objectives of the study, applied methodology, scope and limitations, a grant chart of the project timetable, and description of the work assignments of each group member. An executive summary delves on the background of the organization, the corporate and legal name, and other relevant matters. An account of the status and growth trends of the hospital business will be embarked upon as well as the rationale for the undertaking. Moreover, the executive summary will discuss briefly the findings and recommendations for the marketing, technical, management and financial aspects. The aforementioned major aspects will be discussed comprehensively in this paper. The marketing study ascertains the actual and future demand of the product, competition, selling price, marketing plans, and involves the study of current and projected supply and demand set-up. The technical study aims to choose the process to be used, plant capacity, lay-out, machinery and equipment, operating requirements, and other technical considerations to attain cost minimization and profit minimization. The study of management assists in the selection of business structure, personnel set-up, and internal policies of an enterprise for an effective operations. The financial study quantifies the results of marketing, technical and management phases and expresses in peso terms the possible profitability of the project. Finally, the economic benefits amd social desirability will be evaluated to determine the project's contribution to the national economy as a whole, for in the government, feasibility means social desirability.